Ultrasound's Role in Pediatric Long-Bone Fracture Detection: Emergency Applications - Yahia saleh almansour, Hassan saleh almansour, mohammed mubarak alabbas, Hamad saleh almansour (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Long-bone fractures are among the most common injuries encountered in pediatric trauma, constituting approximately 4% of emergency department visits annually in the United States. These fractures pose risks of hemorrhage and neurovascular compromise, underscoring the importance of timely detection and management to prevent limb loss and morbidity. While conventional radiography remains the primary modality for assessing long-bone injuries, emergency ultrasound offers distinct advantages such as rapidity, non-invasiveness, and absence of ionizing radiation exposure, particularly crucial in pediatric patients vulnerable to radiation-related malignancies.Objective: This study aimed to evaluate the concordance between emergency physicians' and radiologists' assessments of suspected pediatric long-bone fractures using emergency ultrasound and radiography, respectively.Methods: A prospective study was conducted involving pediatric patients (aged ≤18 years) presenting with suspected long-bone fractures. Patients with previous fractures, limb deformities, orthopedic hardware, or open fractures were excluded. Investigators received focused training in ultrasound fracture identification and localization.Results: Fifty-three subjects (mean age: 10.2 years; 56.6% male) underwent 98 ultrasound examinations, primarily targeting upper (70.4%) and lower (29.6%) extremities. Radiography identified 43 fractures. Ultrasound exhibited a sensitivity of 95.3% (95% CI: 82.9%–99.2%) and specificity of 85.5% (95% CI: 72.8%–93.1%) in fracture detection, with positive and negative predictive values of 83.7% (95% CI: 68.8%–92.2%) and 96% (95% CI: 84.9%–99.3%), respectively. Diaphyseal fractures were detected with 100% sensitivity, while near-joint fractures were identified in 93.1% of cases. Ultrasound accurately identified all radiographically confirmed displacements requiring reduction, with sensitivity and specificity of 100% (95% CI: 51.7%–100.0%) and 97.3% (95% CI: 84.2%–99.9%), respectively.Conclusions: Emergency department-performed ultrasound demonstrated superior accuracy in diagnosing diaphyseal fractures compared to metaphyseal and/or epiphyseal fractures in pediatric patients. Its high sensitivity and specificity, along with its ability to identify fractures requiring reduction, support its utility in evaluating suspected long-bone fractures in children